Molecular detection of TT virus and SEN virus infections in hemodialysed patients and blood donors in south of Iran - Rouhi Afkari; Aliyar Pirouzi; Mehdi Mohsenzadeh; Mohammad Azadi; Mohammad Jafari (Wolters Kluwer Medknow Publications, 2012)
Background: SEN virus (SEN-V) and TT virus (TTV) have been classified in the circoviridae family. Both are single-stranded, non-enveloped DNA viruses of about 3800 nucleotides. Patients on maintenance hemodialysis (HD) have a high risk of blood-borne viral infections. SEN-V and TTV has been reported from a number of HD units from various countries throughout the world. Materials and Methods: A total of 377 blood samples obtained from 150 healthy donors and 227 HD patients were collected at the HD center. SEN-V and TTV DNA was determined by polymerase chain reaction (PCR) in all samples. Results: TTV was detected in 109 (48.01%) of 227 hemodialysed patients and 14 (9.33%) of 150 voluntary blood donors (significant, P < 0.05). The PCR results for SEN-V-D/H DNA showed that 65 (28.63%) were positive for SEN-V-D and 33 (14.53%) were positive for SEN-V-H. 9.69% of 227 patients were positive for SEN-V-D/H co-infection. In the control group, SEN-V-D was detected in 14 (9.33%) and SEN-V-H was detected in 15 (10%) of the 150 (100%) blood donors. Conclusion: These findings show that the prevalence of SEN-V-D/H and TTV is higher than healthy blood donors. Also, these results indicate that the prevalence of SEN-V and TTV infections in our region is similar with that in other countries.